Retroperitoneal paraganglioma with hypertensive crisis during laparoscopic surgery - Taichi Fukuzawa; Satoshi Yamaki; Masahiro Irie; Hideyuki Sasaki; Hironori Kudo; Megumi Nakamura; Ryo Ando; Ryuji Okubo; Yuki Endo; Masatoshi Hashimoto; Keisuke Tada; Yudai Nakajima; et al. (Elsevier, 2021)
Pheochromocytoma (PCC) and paraganglioma (PGL) are rare neuroendocrine tumors that arise from chromaffin cells. We report the case of an 11-year-old boy with no history of hypertension who presented with an abdominal mass arising from the retroperitoneum. During laparoscopic surgery, the patient developed a hypertensive crisis with a peak systolic blood pressure of over 270 mmHg, although we were able to continue to perform laparoscopic resection. Even if no concomitant symptoms due to catecholamine production are observed before surgery, as in this case, blood pressure may fluctuate during surgery. Intraoperative and postoperative management should be considered in cooperation with anesthesiologists.